2021
DOI: 10.1186/s13018-021-02586-0
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive plate osteosynthesis with dual plating for periprosthetic distal femoral fractures following total knee arthroplasty

Abstract: Introduction Adequate treatment for periprosthetic distal femur fractures is challenging because of various reasons, including severe osteoporosis and distal fragments that are too small or too distal. We have introduced a new surgical technique for dual plating of periprosthetic distal femur fractures following total knee arthroplasty (TKA) and determined the clinical and radiological outcomes of minimally invasive plate osteosynthesis (MIPO) with a dual locking compression plate (LCP). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…In a study by Kanabar et al, the time for union ranged from 12 to 19 weeks [ 20 ]. Similar results were found in a study done in 2021 by Park et al, where the mean time for the union was 18.4 weeks [ 21 ]. Another study by Kim et al in 2017 revealed that the mean time for the union was 17.1 weeks [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In a study by Kanabar et al, the time for union ranged from 12 to 19 weeks [ 20 ]. Similar results were found in a study done in 2021 by Park et al, where the mean time for the union was 18.4 weeks [ 21 ]. Another study by Kim et al in 2017 revealed that the mean time for the union was 17.1 weeks [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…al., the time for union ranged from 12 to 19 weeks[20]. Similar results were found in a study done in 2021 byPark et al., where the mean time for the union was 18.4 weeks[21]. Another study byKim et al in 2017 revealed that the mean time for the union was 17.1 weeks[22].Of note, 24 cases (80%) had full flexion achieved at or above 120 degrees, while four patients (14.5%) had flexion between 90 and 120 degrees and the remaining two patients had flexion below 90 degrees.…”
supporting
confidence: 85%
“…Four studies using the DP technique were included for the final data analysis. 6,32,37,38 Cicek et al reported on a series of 22 patients treated with the DP technique for Su type III fractures. 6 The mean time to union was 4.3 mo (SD ± 0.9 mo).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported excellent function (KSS 94 and KSFS 89.5) and fewer complications for very low PPDFFs using double-locked plating. 27 In addition, dual plating with minimal invasion or intramedullary fibular strut allograft has shown satisfactory outcomes. 26 , 27 However, these were observational studies without control groups.…”
Section: Discussionmentioning
confidence: 99%
“… 27 In addition, dual plating with minimal invasion or intramedullary fibular strut allograft has shown satisfactory outcomes. 26 , 27 However, these were observational studies without control groups. Further research comparing the double-locking plate and DFR for low PDFFs is required.…”
Section: Discussionmentioning
confidence: 99%